The measurement of un-signalized intersection elasticity of a traffic system for a new park-and-ride - Zhang, Hui (2016)
Park-and-ride is one of the popular ways to improve traffic condition. Park-andride was supposed to be built at the edge of the town as to reduce traffic congestion in town, if the P&R is built inside the town, it may attract more traffic into the town unnecessarily and inevitably increases traffic congestion. This means the traffic system is inelastic to the proposed P&R and for the case of Park-and-Ride in Klang Town, it is interesting to measure how elastic the traffic system to the provision of a new P&R within the town center. This research paper will study the impact of new KTM Klang Commuter Station Park and Ride to existing traffic congestion. The selected study area is around Klang KTM commuter Station, and the new park-and-ride will be built beside the KTM station. This site is chosen because it is located near to public transportation facilities, which is Klang KTM commuter Station. The selected study area is a chain of un-signalized intersections leading to Klang KTM commuter Station, in which the proposed site of the park-and-ride is located. This research aims to establish existing condition of traffic system of the study and based on Li M. X and Chen J.W. (2000) research and Malaysia Highway Capacity Manual to calculate the maximum capacity and the maximum control delay for each intersection to measure the elasticity of the intersection. Based on the existing traffic condition and intersection elasticity to propose upgrading plan for the inelastic intersection.